MAQASHID SYARIAH DALAM EKONOMI: TINJAUAN KRITIS ATAS PEMIKIRAN ASY-SYATIBI - Anisa, Lina Nur (Commodity : Jurnal Perbankan dan Keuangan Islam, 2024)
This article examines the significant role of maqashid syariah in Islamic economic thought, particularly through the contributions of Asy-Syatibi. Maqashid Syariah, emphasizing the general welfare, serves as a core principle in developing an equitable and inclusive Islamic economy. The article aims to analyze Asy-Syatibi's economic thought from the perspective of maqashid syariah and assess the relevance of this concept in contemporary Islamic economics. This research employs a qualitative method with a literature review approach, examining various works on the concept of maqashid syariah and a critical analysis of Asy-Syatibi's thoughts in depth.The study concludes that Asy-Syatibi's principles of maqashid syariah can be adapted to shape modern economic policies that are more inclusive and socially just. With proper implementation, these principles have the potential to address current global economic challenges. This study also recommends collaboration between governments and financial institutions to optimize the application of zakat and waqf and to enhance Sharia-based business ethics education, fostering a more sustainable economic system.